Association between depression and anxiety among the COPD patients in a Nepalese community hospital: a cross sectional study - Shakya, Regan; Gautam, Bandana (Birat Journal of Health Sciences, 2020)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a progressive disabling illness characterized by persistent airflow limitation affecting physical, psychological and social aspect of the individual. Amongst the associated co morbidities, depression and anxiety has been identified as common modifiable psychiatric comorbidities of COPD which impacts the patient’s quality of life. Objectives: To establish the prevalence of depression and anxiety among the COPD patient and determine the association between them. Methodology: The cross sectional study was conducted at Dhulikhel Hospital. We used a convenient sampling method to recruit seventy three COPD participants admitted in the Medicine ward. We interviewed the participants to evaluate anxiety and depression using the Nepali version of Hospital Anxiety and Depression Scale questionnaire. We considered positive result of anxiety and depression when the Hospital Anxiety and Depression score was above eight. Results: Depressive and Anxiety symptoms were observed in 30 % and 33% of the participants respectively. Similarly 20% of the participants had both the symptoms of depression and anxiety. The association between depression and anxiety was found to be highly significant (p<0.001). In the multivariate model the odds of depression and anxiety was nine percent increase with every one year increase in age after adjusting for gender and duration of illness. (adjusted OR: 1.07; CI 1.00- 1.17; p-value: 0.03). In an unadjusted model depression was significantly associated to every year increase in age (unadjusted OR: 1.07; CI: 1.00- 1.13; p-value: 0.03) Conclusion: Depression and anxiety is prevalent among COPD patient at Dhulikhel hospital with one fifth of the patient demonstrating both depression and anxiety symptoms.